2018
DOI: 10.1371/journal.pone.0201170
|View full text |Cite
|
Sign up to set email alerts
|

Tissue-resident NK cells differ in their expression profile of the nutrient transporters Glut1, CD98 and CD71

Abstract: Metabolism is a critical basis for immune cell functionality. It was recently shown that NK cell subsets from peripheral blood modulate their expression of nutrient receptors following cytokine stimulation, demonstrating that NK cells can adjust to changes in metabolic requirements. As nutrient availability in blood and tissues can significantly differ, we examined NK cells isolated from paired blood-liver and blood-spleen samples and compared expression of the nutrient transporters Glut1, CD98 and CD71. CD56b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
53
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 54 publications
(56 citation statements)
references
References 56 publications
2
53
0
Order By: Relevance
“…CD56 bright cells, probably by virtue of increased cytokine receptor expression, are more responsive to metabolic change and upregulated several metabolic markers more strongly that CD56 dim cells in response to cytokine stimulation . Recently, this has been confirmed for peripheral blood NK cells and extended with similar findings among tissue resident (CD56 bright , liver or spleen) NK cells . Within the CD56 dim subset, further subsets can be further discriminated.…”
Section: What About Nk Cell Metabolism?mentioning
confidence: 60%
See 3 more Smart Citations
“…CD56 bright cells, probably by virtue of increased cytokine receptor expression, are more responsive to metabolic change and upregulated several metabolic markers more strongly that CD56 dim cells in response to cytokine stimulation . Recently, this has been confirmed for peripheral blood NK cells and extended with similar findings among tissue resident (CD56 bright , liver or spleen) NK cells . Within the CD56 dim subset, further subsets can be further discriminated.…”
Section: What About Nk Cell Metabolism?mentioning
confidence: 60%
“…In particular, glutamine uptake through SLC7a5, an amino acid transporter that is strongly upregulated on NK cells in response to cytokine, was key for activation and maintenance of c‐Myc signaling. There is increasing evidence that nutrient receptors, such as the transferrin receptor (CD71), l ‐amino acid transporter SLC7a5 (also known as LAT1; it is the active subunit that forms a heterodimer with the chaperone chain, CD98), the glutamine transporter (SLC1a5), as well as the glucose transporter (Glut1), are all expressed and upregulated on activated NK cells where they can impact on immune signaling …”
Section: What About Nk Cell Metabolism?mentioning
confidence: 99%
See 2 more Smart Citations
“…A number of studies have demonstrated that CD56 bright cells are more metabolically responsive, whether they are from peripheral blood or tissue resident [22,27]. While CD98 is expressed on all NK cells (and is upregulated in response to cytokine), CD71 is generally only present at low levels and increases preferentially on CD56 bright cells upon activation.…”
Section: Specialised Nk Cell Subsets Differ In Their Metabolic Profilesmentioning
confidence: 99%